Pengaruh Penyaluran Kredit Perbankan Terhadap Pertumbuhan Ekonomi di Nusa Tenggara Timur Tahun 2013 – 2022 - Ridho Christiadi Simbolo; Amanda Putri; Elfira Erlikasna Br Tarigan; Safira Kencana Putri; Aldivo Anugraha; Nurlela Nurlela; Disya Ayu Rivtryana (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Banking plays a crucial role in society. Banks, as direct partners of the community, serve as the main drivers of the economy. The significance of the banking sector in shaping development directions, fostering economic growth, and enhancing societal welfare has been acknowledged by various societal elements. This study aims to examine the regression outcomes of variables such as working capital loans, investment loans, and consumer loans on economic upliftment in the region of East Nusa Tenggara Province. Multiple linear regression analysis, t-tests, and F-tests are employed as statistical methods to discern the relationships between several independent variables and the dependent variable in this research. Secondary data spanning a decade are collected from the Central Bureau of Statistics of East Nusa Tenggara Province. The findings reveal that economic growth in East Nusa Tenggara Province is positively and significantly influenced by investment loans and consumer loans, while working capital loans exhibit a negative and insignificant impact.